2011
DOI: 10.1128/jb.05223-11
|View full text |Cite
|
Sign up to set email alerts
|

Genome Sequence of the Mercury-Methylating and Pleomorphic Desulfovibrio africanus Strain Walvis Bay

Abstract: Desulfovibrio africanus strain Walvis Bay is an anaerobic sulfate-reducing bacterium capable of producing methylmercury (MeHg), a potent human neurotoxin. The mechanism of methylation by this and other organisms is unknown. We present the 4.2-Mb genome sequence to provide further insight into microbial mercury methylation and sulfate-reducing bacteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 19 publications
2
10
0
Order By: Relevance
“…The PCS genome had a G+C content of 61.2%, which is similar to the 61.4% G+C content reported for strain Walvis Bay (4). Strain PCS shows 95% average nucleotide identity to strain Walvis Bay when the two genome sequences are compared using the JSpecies program (22).…”
Section: Genome Announcementsupporting
confidence: 78%
See 2 more Smart Citations
“…The PCS genome had a G+C content of 61.2%, which is similar to the 61.4% G+C content reported for strain Walvis Bay (4). Strain PCS shows 95% average nucleotide identity to strain Walvis Bay when the two genome sequences are compared using the JSpecies program (22).…”
Section: Genome Announcementsupporting
confidence: 78%
“…The isolated strain was Gram negative, motile, nonsporulating, and 99% similar by 16S rRNA gene sequencing to Desulfovibrio africanus subsp. uniflagellum (GenBank accession number EU659693) and D. africanus strain Walvis Bay (CP003221.1) (4), which is consistent with the species definition (5). D. africanus strains, including PCS, have different morphotypes associated with a cell cycle (6–10), and PCS incompletely oxidizes lactate, accumulating acetate as an end product.…”
Section: Genome Announcementsupporting
confidence: 77%
See 1 more Smart Citation
“…Recent studies have shown that most of the commonly studied Desulfovibrio strains align into a clade with few Hg methylators, while most of the Hg methylating strains fall into the halophiles group 20 . The finished genomes for Desulfovibrio strain ND132, Desulfovibrio africanus strain Walvis Bay and Desulfovibrio africanus strain PCS are the first complete genomes for the strains that generate MeHg 38 39 40 . This will aid in to our studies with comparison of full genomes of known Hg methylators identified in DWW and comparative metagenomics of Hg contaminated ecosystems.…”
Section: Resultsmentioning
confidence: 99%
“…Significant advances in our knowledge of the microbial Hg methylation process have been made over the last two decades (e.g., Gilmour and Henry, 1991 ; Choi and Bartha, 1993 ; Choi et al, 1994a , b ; Ekstrom et al, 2003 ; Schaefer and Morel, 2009 ; Brown et al, 2011a , b ; Gilmour et al, 2011 ; Parks et al, 2013 ). Still, major gaps persist in our understanding of the geochemical forms of inorganic Hg available for biomethylation (Benoit et al, 2003 ; Jonsson et al, 2012 ; Hsu-Kim et al, 2013 ), the biochemical pathways involved (Landner, 1971 ; Choi et al, 1994b ; Poulain and Barkay, 2013 ), and the mechanism for uptake of Hg by methylating microbes (Benoit et al, 1999 , 2001a ; Schaefer and Morel, 2009 ; Bridou et al, 2011 ; Schaefer et al, 2011 , 2014 ; Pedrero et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%